Treatment of Long Standing Bilateral Temporomandibular Joint Ankylosis with Condylar Prosthesis - Hassan, Syed Sirajul (Springer India, 2010)
INTRODUCTION: TMJ ankylosis is a condition which results in partial to complete inability to open the mouth due to fusion of head of condyle and glenoid fossa. CASE REPORT: A 28 year old man reported to our department with a complaint of inability to open mouth since 13 years. On basis of clinical examination, radiographs and CT scans, he was diagnosed with complete bilateral bony TMJ ankylosis. The treatment plan included bilateral condylectomy with coronoidectomy through a combination of endaural and rhytidectomy incision and interpositional grafting with temporalis myofascial flap. Reconstruction of the TMJ was done with specially designed stainless steel partial condylar prosthesis. Extended genioplasty was done to advance the chin. Post-operative early physiotherapy was initiated with a custom made oral physiotherapy device. Complete oral rehabilitation was done with fixed partial dentures, and patient is on regular follow up. RESULTS: Patient had mouth opening of 29 mm and also had a satisfactory esthetic appearence.